A comparison of compliance in the estimation of body fluid status using daily fluid balance charting and body weight changes during continuous renal replacement therapy - Davies, Hugh; Leslie, Gavin; Morgan, D.; Dobb, G. (Elsevier Inc, 2018)
© 2017 Australian College of Critical Care Nurses Ltd. Background: The risk of fluid overload and mortality is increased in patients with severe acute kidney injury. Charting of daily fluid balance is a key component of fluid assessment but not without problems affecting accuracy. The introduction of electronic bed scales has made routine patient-weighing easier and focused attention on monitoring fluid-related weight changes. Objectives: This paper investigated the frequency of compliance in weighing patients daily using electronic bed scales and evaluated the relationship between calculated fluid balance and body weight changes in patients receiving continuous renal replacement therapy (CRRT). Methods: A prospective cohort interventional observation study was conducted in a tertiary ICU between June 2015 and February 2016. All patients who required CRRT, > 18 years with an admission > 24 hours were enrolled. Each patient was able to be weighed daily using electronic bed scales. At the same time daily fluid balances were calculated using paper-based charting. Trends in compliance of recording body weight changes with daily charting of fluid balances was observed until patient no longer required CRRT. Daily differences were compared using Pearson correlation and Bland-Altman analysis. Results: A total of 61 patients were recruited. Four hundred and three days of CRRT was recorded with 286 days (71%) accompanied by a measured body weight. One hundred and eighty-one paired comparisons between body weight change and corresponding fluid balance was obtained from 39 patients (64%). Correlation between changes in body weight with fluid balance was weak (r = 0.34, p. < . .0001). On Bland-Altman analysis mean bias was 0.18. kg (95% CI -ve8.9 to +ve8.6. kg). Conclusion: Change in body weight offers an alternative to charting inputs and outputs in monitoring fluid balance. A physical representation of fluid status is provided rather than a calculated value. Lack of compliance in weighing of patients on two consecutive days was shown to reduce utility as a routine monitoring practice. The relationship between fluid balance and changes in body weight was not strong.